Application of l‐asparaginase to produce high‐quality Turkish coffee and the role of precursors in acrylamide formation. Issue 6 (14th April 2021) - Akgün, Banu; Arıcı, Muhammet; Çavuş, Filiz; Karataş, Ayşe Binnur; Ekşi Karaağaç, Hacer; Uçurum, H. Özgül
Abstract: In this study, the optimized conditions for l ‐asparaginase treatment on Arabica coffee beans and the impacts of two independent variables (enzyme dosage and treatment time) on five dependent variables (acrylamide, 2‐Acetyl‐3‐Methylpyrazine, 2, 3‐Dimethylpyrazine, 2, 5‐Dimethylpyrazine, and 2‐Methylpyrazine) were investigated by employing RSM. Green coffee beans were treated with l ‐asparaginase at various dosages (0–4000 ASNU/kg green bean) and times (30–120 min). Statistical analysis indicated that levels of responses were significantly related to enzyme dosage and treatment time ( p <  .05). These independent parameters had a significant influence on the quantity of acrylamide in Turkish coffee ( p <  .05), but enzyme dosage was found to be more effective ( p <  .01). The optimum conditions of l ‐asparaginase treatment for producing superior quality Turkish coffee were determined as 2, 126.4 ASNU/kg green bean and 82.73 min. Also, a moderate positive correlation (r = 0.669, p  < .01) was found between the asparagine concentration in green coffee beans and acrylamide content of coffees produced from these beans. Practical applications: The use of asparaginase seems a good solution for acrylamide mitigation in foods. However, various factors including application dosage and time should be taken into consideration when using this enzyme in food manufacture. There is a need to examine the effect of these parameters to optimize the enzyme application conditions in coffee beans. Knowledge about optimum conditions for asparaginase treatment may be applied in the production of high‐quality Turkish coffee with low acrylamide and high pyrazine concentration.